2021
DOI: 10.1101/2021.04.20.440666
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Continuous multiplexed population representations of task context in the mouse primary visual cortex

Abstract: Primary visual cortex (V1) neurons integrate motor and multisensory information with visual inputs during sensory processing. However, whether V1 neurons also integrate and encode higher-order cognitive variables is less understood. We trained mice to perform a context-dependent cross-modal decision task where the interpretation of identical audio-visual stimuli depends on task context. We performed silicon probe population recordings of neuronal activity in V1 during task performance and showed that task co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…This dissimilarity between spontaneous and sensory-driven patterns increases across zebrafish development (Avitan et al, 2021). Other internally generated signals, such as task context and behavioral choice, are also represented by neural directions orthogonal to sensory-driven patterns (Goris et al, 2017;Hajnal et al, 2021;Zhao et al, 2020). Together, these studies suggest that sensory areas process information on a background of high-dimensional SA that can represent many variables.…”
Section: Spontaneous Activity and Its Potential Functional Rolesmentioning
confidence: 89%
See 3 more Smart Citations
“…This dissimilarity between spontaneous and sensory-driven patterns increases across zebrafish development (Avitan et al, 2021). Other internally generated signals, such as task context and behavioral choice, are also represented by neural directions orthogonal to sensory-driven patterns (Goris et al, 2017;Hajnal et al, 2021;Zhao et al, 2020). Together, these studies suggest that sensory areas process information on a background of high-dimensional SA that can represent many variables.…”
Section: Spontaneous Activity and Its Potential Functional Rolesmentioning
confidence: 89%
“…(E) The discriminant direction in neural population space which best distinguishes between visual stimuli was found to be orthogonal to the discriminant direction which best distinguishes the context of the task (visual or auditory) in a context-dependent behavioral task in mice (Hajnal et al, 2021).…”
Section: D Ementioning
confidence: 99%
See 2 more Smart Citations
“…Note that we had already shown that arousal and locomotion could not account for those results ( McClure and Polack, 2019 ), and we therefore did not consider those parameters further in this study. Moreover, several studies have recently demonstrated that the modulation of the V1 neuronal activity by behavioral parameters such as locomotion and arousal are orthogonal to orientation encoding ( Hajnal et al, 2021 ; Stringer et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%